Implikasi Pembentukan Produk Hukum Daerah Terhadap Penertiban Kenderaan Angkutan Becak Motor (Bentor) - Awaludin S. Habibie; Asdar Arti; Rusmulyadi Rusmulyadi (Jurnal Litigasi Amsir, 2024)
The study examines the impact of regional regulations on motorized becak (Bentor) transportation, focusing on Regional Regulation Number 6 of 2006. It finds that while these regulations affect community order and local traditions, they lack adequate legal protection and safety measures for passengers. The research, conducted through empirical normative legal methods, highlights a need for improved legal awareness and enforcement due to numerous traffic violations and Bentor accidents. The study suggests a review of the regulation's substance to accommodate better the unique characteristics and needs of Bentor transportation within Gorontalo Province.